Mathematical modeling and optimization of cam mechanism in delivery system of an offset press. (April 2017) - Ouyang, Tiancheng; Wang, Pan; Huang, Haozhong; Zhang, Ning; Chen, Nan
Abstract: This paper presents a new method for cam profile design and optimization by integrating a single objective optimization procedure with a dynamic model of cam-follower mechanism in delivery system of an offset press. The proposed approach based on a new strategy mainly includes two parts, a single objective optimization procedure for the kinematic characteristics of the follower and a dynamic model for the cam-follower mechanism. For the first part, the follower acceleration profile is described by modified trapezoidal curve, thereby deriving the velocity, jerk and displacement functions, respectively. Then sequential quadratic programming (SQP), which deals well with equality and inequality constrains, is adopted as the single objective optimized algorithm in this part. In the second part, a two degrees of freedom lumped parameter model taking into account the torsional flexibility and damping of the grippers, the contact compliance at the cam/roller and grippers/block interfaces, is established to investigate the dynamic behavior of the force-closed cam-follower mechanism. In order to improve the kinematic and dynamic characteristics of cam-follower mechanism synthetically, an optimization cycle, known as iterative process, is introduced to implement the procedure of single objective optimization and dynamic simulation alternately. The example illustrated in this paper, sufficiently demonstrates the effectiveness of the new method. Ultimately, the proposed approach gives cam designers a useful tool to design and optimize the cam profile, so as to reduce residual vibration. Highlights: A modified trapezoidal curve with an adjustable positive and negative acceleration is adopted to describe the multiple-dwell follower profile in delivery system of an offset press. A two degrees of freedom dynamic model which takes into account the torsional flexibility and damping of the cam and grippers, the contact compliance at the cam/roller and grippers/block interfaces, is established. A new method integrated a single objective optimization procedure with a dynamic model is introduced to improve the kinematic and dynamic characteristics of cam-follower mechanism. Comparisons are made between the original design and the optimal programme.